1974
DOI: 10.1042/bj1400047
|View full text |Cite
|
Sign up to set email alerts
|

Co-operative action by endo- and exo-β-(1→3)-glucanases from parasitic fungi in the degradation of cell-wall glucans of Sclerotinia sclerotiorum (Lib.) de Bary

Abstract: 1. Two fungi, Coniothyrium minitans Campbell and Trichoderma viride Pers. ex Fr., were grown on autoclaved crushed sclerotia of the species Sclerotinia sclerotiorum, which they parasitize. 2. In vitro the crude culture filtrates would lyse walls isolated from hyphal cells or the inner pseudoparenchymatous cells of the sclerotia, in which a branched beta-(1-->3)-beta-(1-->6)-glucan, sclerotan, is a major constituent. 3. Chromatographic fractionation of the enzymes in each culture filtrate revealed the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
4

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 19 publications
(23 reference statements)
2
41
0
4
Order By: Relevance
“…Synergistic effects between fungal cell wall hydrolases have previously been reported; a cooperative action by several exo-and endo-␤-1,3-glucanases during the degradation of cell wall glucans of Sclerotinia sclerotiorum by T. viride has been suggested (21). In order to demonstrate this result in our system, combinations of the purified ␤-1,6-glucanase-II with other cell wall-degrading enzymes were made and the release of reducing sugars and the clearing activity on different fungal cell walls were assayed.…”
Section: Discussionmentioning
confidence: 95%
“…Synergistic effects between fungal cell wall hydrolases have previously been reported; a cooperative action by several exo-and endo-␤-1,3-glucanases during the degradation of cell wall glucans of Sclerotinia sclerotiorum by T. viride has been suggested (21). In order to demonstrate this result in our system, combinations of the purified ␤-1,6-glucanase-II with other cell wall-degrading enzymes were made and the release of reducing sugars and the clearing activity on different fungal cell walls were assayed.…”
Section: Discussionmentioning
confidence: 95%
“…Their nutritional function is evident by the extracellular degradation of 1,3-/?-glucans serving as carbon sources (Bamforth, 1980;Stahmann et al, 1992). Parasitic fungi may use them for degradation of the host cell wall (Jones et al, 1973;Bodenmann et al, 1984). Their involvement in fungal cell wall formation during hyphal tip growth, as tightly balanced antagonists of glucan synthase, is controversial (Bartnicki-Garcia, 1968Wessels, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…However, information on the cell wall-degrading hydrolases of C. minitans is sparse. Although earlier studies (23) showed the presence of two synergistically interacting glucanases in the culture filtrate of this fungus, no data on the physicochemical properties, inducibility, and genetic background of these enzymes have been available.…”
Section: Discussionmentioning
confidence: 91%
“…According to Philips and Price (43), penetration is achieved merely by physical pressure exerted by the mycoparasite. However, other workers have claimed that penetration is facilitated by the production of cell wall-degrading enzymes by the fungus (21,23).…”
Section: Coniothyrium Minitansmentioning
confidence: 99%